2021
DOI: 10.2147/ndt.s302443
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Formula Xiaoyaosan Alleviates Depressive-Like Behavior in CUMS Mice by Regulating PEBP1-GPX4-Mediated Ferroptosis in the Hippocampus

Abstract: Background At present, the pathogenesis of depression is not fully understood, and nearly half of depression patients experience no obvious effects during treatment. This study aimed to establish a depression mouse model to explore the possible role of ferroptosis in the pathogenesis of depression, and observe the effects of Xiaoyaosan on PEBP1-GPX4-mediated ferroptosis in the hippocampus. Methods Forty-eight male C57BL/6 mice were randomly divided into a control group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 94 publications
(107 reference statements)
0
23
0
Order By: Relevance
“…Genes involved in ferroptosis were differentially regulated; specifically, glutathione peroxidase (GPX4, necessary for repairing oxidative damage) was downregulated after CUMS suggesting a role of ferroptosis in the phenotype of depression. In addition, this study also showed that fluoxetine not only resolved depressive behaviors but also restored normal ferroptosis signaling ( 360 ). Experimental models also display an increase in iron load in the brain which results in anxiety symptoms.…”
Section: Metabolic Pathways In Microgliamentioning
confidence: 62%
“…Genes involved in ferroptosis were differentially regulated; specifically, glutathione peroxidase (GPX4, necessary for repairing oxidative damage) was downregulated after CUMS suggesting a role of ferroptosis in the phenotype of depression. In addition, this study also showed that fluoxetine not only resolved depressive behaviors but also restored normal ferroptosis signaling ( 360 ). Experimental models also display an increase in iron load in the brain which results in anxiety symptoms.…”
Section: Metabolic Pathways In Microgliamentioning
confidence: 62%
“…The research on the mechanism and the treatment of anxiety and depression have also attracted extensive attention. Jiao et al [95] found that the contents of total iron and ferrous ion in the hippocampus of chronic unpredictable mild stress (CUMS) model mice increased, and GPX4, FTH1, ACSl4, and COX-2 also changed significantly, which proved the evidence of ferroptosis in the hippocampus of the depression mouse model. Previous research reported that sodium hydrosulfide (NaHS) can alleviate the depressive and anxiety-like behaviors induced by type 1 diabetes mellitus (T1DM) [96].…”
Section: Ferroptosis In Anxiety and Depressionmentioning
confidence: 97%
“…8,10,15,45 In other animal research studies, such as those focusing on olfactory bulbectomized (OBX)-induced depression and chronic unpredictable mild stress (CUMS)-induced depression, there was a marked increase in the expressions of Iba1 and GFAP, which indicate the activation of microglia and astrocytes, respectively. 46,47 Interestingly, available evidence from previous studies also shows that activated microglia and astrocytes are found to be intimately involved in depression. 48 Also consistent with the previous findings, we observed that astrocytes and microglia were activated and the mRNA expressions of TLR-4, iNOS, Cox-2, TNF-α, IL-6 and IL-1β in the cortex were notably enhanced, while in the mice administered sesamol, microglia and astrocyte activation was inhibited as well as there was an increase of inflammatory cytokines (Fig.…”
Section: Food and Function Papermentioning
confidence: 99%